Pancasila, Environmental Protection, and Religious Movements: How Can Pancasila Education in Islamic Boarding Schools Promote Environmental Sustainability? - Muhammad Ahsanul Fikri; Yulia Ayu Savitri (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2022)
The concept of Pancasila education has been widely adopted in various educational units, including in the Islamic boarding school education model, both in Indonesia and in Cambodia. The concept of Pancasila Education in Indonesia and Moral and Character Education in Cambodia have something in common, namely both emphasizing on strengthening student values ​​for the values ​​of the entire nation, including the value of environmental conservation. This paper aims to describe and analyze how Pancasila Education in Indonesia and Moral and Character Education in Cambodia at Islamic Boarding Schools are related to the promotion of environmental sustainability. This research proves that Islamic and national values ​​are able to encourage students' awareness in carrying out a massive movement towards environmental protection. Simple and nature-oriented lifestyles are emphasized in Islamic boarding schools, such as modesty in dress, food consumption, and wise use of natural resources. In addition, Islamic values ​​also encourage the obligation of a Muslim in preserving the environment as one of the entities of life and God's creation.